Transition between monoclinic and tetragonal _ phases induced by reactive oxygen gas in RF-sputtered V2O5 thin films - S. Tipawan Khlayboonme (My University, 2022)
Thin films of V2O5 are promising materials for applications in chromogenic devices, such as gas sensors and contactless optical thermal sensors. Therefore, controlling the formation of the various phases of V2O5 is important. The device performance, in relation to satisfactory coloration efficiency and fast response, strongly depends on the characteristics of the phase incorporated in the film structure. To better understand the phase formation in these films, thin films of V2O5 were deposited by RF magnetron sputtering using an O2-reaction technique from a metallic V target, and the influence of RF power and O2 levels on the transition between the β-monoclinic and β-tetragonal phase structures was investigated by X-ray diffractometer. The films were also evaluated using Auger-electron, Raman-, and UV-vis spectrometers to determine their composition, chemical, and electronic properties to assess the effects of the two sputtering parameters. The mechanism underlying the development of film properties is related to the plasma characteristics and species observed by optical emission spectroscopy. Increasing the RF power resulted in a higher phase content of the β-monoclinic and α-orthorhombic phase, whereas an increasing the oxygen levels induced a phase transition towards the β-tetragonal phase of V2O5. Films with different phase contents exhibited different optical energy bandgaps. Plasma diagnostics showed that increasing the RF power increased the thickness of plasma sheaths on the target surface. The thinner sheath on the target surface further increased the β-tetragonal phase content. The variation between β-monoclinic and β-tetragonal phase content was expected because of the bombardment of energetic O− ions that were accelerated from the plasma sheath toward the growth surface. A deeper understanding of the transition between β phases in V2O5 films can enable better phase control, which can improve film application towards various sensing devices, particularly chromic- or temperature-sensors.
Keywords: Monoclinic crystal system; Tetragonal crystal system; Orthorhombic crystal system; Transition Metal Oxide Nanomaterials